Investigation of the behavior of box-shaped deep foundations - Günay, Serdar. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
A box-shaped deep foundation is a new type of deep foundation, which consists of a raft structurally connected to outer walls that encompass the soil. Walls and the raft together create a structure that functions much like an inverted “box” in physical terms. The walls beneath the raft are anticipated to serve as a frame to restrain lateral motion. BSDFs employ the enclosed soil core as an integrated load-transfer element. This study initially aimed to investigate the behavior of BSDFs in sand under vertical static loads through an extensive numerical analysis utilizing a 3D FEM. Two coefficients which are BCR and SRR have been developed to better interpret the load-settlement behavior of BSDFs with different geometries, soil types and interface roughness. The presence of a soil core in a BSDF adds complexity to evaluate its load-settlement mechanism. Within the scope of this study, the quasi-monolithic behavior of BSDFs has also been examined by comparing them to embedded foundations, with the assumption that embedded foundations exhibit a complete monolithic behavior. The MBR and MSR values act as indicators for assessing the extent to which a BSDF exhibits monolithic behavior. As the MBR and MSR values approach one, it signifies that the BSDF behaves increasingly like a monolithic compound body. Furthermore, a laboratory testing program was conducted to observe the load-settlement behavior and monolithic performance of model BSDFs for a validation of the numerical analyses. Secondly, an extensive numerical analysis consisting of 195 different models was carried out to compare the efficiency of BSDFs to CPRFs. Based on the efficiency concept outlined in this study, it can be inferred that BSDFs may serve as a viable alternative to CPRFs in various scenarios. The findings of this study are expected to enhance comprehension of this emerging foundation type and hold the potential to facilitate its practical implementation. The visuals that emerged within the scope of this thesis study and whose copyright was transferred to the publishing house have been used in the thesis book in accordance with the publishing policy regarding the reuse of the author's own produced texts and graphics, available on the publisher's web page.
Keywords: Foundations.; Civil engineering.